Current Debates on Infrastructure Policy - Estache, Antonio (World Bank, Washington, DC, 2012)
This paper provides an overview of the major current debates on infrastructure policy. It reviews the evidence on the macroeconomic significance of the sector in terms of growth and poverty alleviation. It also discusses the major institutional debates, including the relative comparative advantage of the public and the private sector in the various stages of infrastructure service delivery as well as the main options for changes in the role of government (i.e. regulation and decentralization).